2020
DOI: 10.1101/2020.08.31.276428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Biological Noise in an Organelle Size Control System

Abstract: Stochastic variations (noise) in gene expression have been extensively characterized, but the ramifications of this gene-level variation for cellular structure and function remain unclear. To what extent are cellular structures subject to noise? We show that flagellar length in Chlamydomonas exhibits significant variation that results from a combination of intrinsic fluctuations within the flagella and extrinsic cell to cell variation. We analyzed a series of candidate genes affecting flagella and found that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Similar principles may underlie the length control of other polarized, linear actin structures, such as filopodia and stereocilia. Further, related strategies may be used to control the growth of radial microtubule arrays that reach the cell periphery ( 25 , 26 ), and may explain the scaling relationships observed between flagellar length and cell length ( 27 ) and between contractile ring diameter and cell diameter ( 28 ).…”
Section: Main Textmentioning
confidence: 99%
“…Similar principles may underlie the length control of other polarized, linear actin structures, such as filopodia and stereocilia. Further, related strategies may be used to control the growth of radial microtubule arrays that reach the cell periphery ( 25 , 26 ), and may explain the scaling relationships observed between flagellar length and cell length ( 27 ) and between contractile ring diameter and cell diameter ( 28 ).…”
Section: Main Textmentioning
confidence: 99%
“…Organelle biogenesis, among the most complex tasks the eukaryotic cell performs, is the result of the coordinated synthesis of tens to hundreds of protein and lipid macromolecular species, each of which is potentially subject to stochastic fluctuations intrinsic to their production. How these molecular-scale fluctuations propagate to organelle-scale functional properties remains an outstanding question in quantitative cell biology (Chang and Marshall 2017, Vagne and Sens 2018, Sachadeva 2016, Bauer 2020. We have previously shown that organelle copy number statistics exhibit substantial cell-to-cell variability (Mukherji and O'Shea 2014), though the root mechanisms of this variability remain subject of much debate (Craven 2016, Choubey 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Uncoordinated regulation of organelle size can lead to severe phenotypic defects, such as impaired Chlamydomonas reinhardtii motility in uncoordinated flagellar length control (McVittie 1972), inappropriately sized secretory vesicles due to variability in Golgi size (Ferraro 2014), and impaired metabolism due to defects in mitochondrial (Toda 2016) and peroxisomal (Waterham 2007) fission among others. What remains underexplored, as also highlighted by complementary work simultaneous to our own documenting the coupling between organelle size and fluctuations (Bauer 2020), is development of a quantitative understanding of the precision with which organelle size variability is controlled, particularly for organelles that exist in multiple copies per cell.…”
Section: Introductionmentioning
confidence: 99%